PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK KREDIT MULTIGUNA TERHADAP KEPUASAN NASABAH KREDIT PADA PT. BPR HOKI CABANG DENPASAR - Suputra, I Gusti Made Ary Bayu; Mandala, Kastawan (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
The purpose of this study was to determine the effect of quality of service and product quality multipurpose loans to credit customer satisfaction at PT. BPR Hoki Region Denpasar. This study used a qualitative research using surveys and questionnaires to 85 respondents customers multipurpose loans PT. BPR Hoki Region Denpasar. The sampling technique uses accidental sampling. Data analysis techniques used in this research is multiple linear regression. It was found that the quality of service and quality of products simultaneously affect the customer satisfaction at PT. BPR Hoki Denpasar. Second, the quality of service and significant positive effect on customer satisfaction at PT BPR Hoki Denpasar. Finally, quality products and a significant positive effect on customer satisfaction at PT BPR Hockey Denpasar.   Keywords : Quality Service, Quality Products, Customer Satisfaction
Keywords: Quality Service, Quality Products, Customer Satisfaction